Phaeochromocytoma Crisis: Two Cases of Undiagnosed Phaeochromocytoma Presenting after Elective Nonrelated Surgical Procedures. (28th October 2013) - Johnston, P. C.; Silversides, J. A.; Wallace, H.; Farling, P. A.; Hutchinson, A.; Hunter, S. J.; Eatock, F.; Mullan, K. R.
Abstract : Phaeochromocytoma is a catecholamine producing tumour and an uncommon cause of hypertension. We present two cases of relatively asymptomatic individuals, in which previously undiagnosed phaeochromocytoma was unmasked by elective nonadrenal surgical procedures, manifesting as postoperative hypertensive crisis and subsequent cardiogenic shock. The initial management in intensive care is discussed, in addition to the clinical and biochemical diagnostic challenges present. Successful adrenalectomy was performed in each case.